2014
DOI: 10.1186/1471-2407-14-450
|View full text |Cite
|
Sign up to set email alerts
|

The genetic basis for inactivation of Wnt pathway in human osteosarcoma

Abstract: BackgroundOsteosarcoma is a highly genetically unstable tumor with poor prognosis. We performed microarray-based comparative genomic hybridization (aCGH), transcriptome sequencing (RNA-seq), and pathway analysis to gain a systemic view of the pathway alterations of osteosarcoma.MethodsaCGH experiments were carried out on 10 fresh osteosarcoma samples. The output data (Gene Expression Omnibus Series accession number GSE19180) were pooled with published aCGH raw data (GSE9654) to determine recurrent copy number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 24 publications
5
39
0
Order By: Relevance
“…And although osteosarcoma tumors show a great deal of SV, SVs were found within only 81 of the druggable genes (30 recurrently). The most common genes with an SV were TP53 (29), LRP1B (14), RB1 (8), and FHIT (8). No potentially in-frame gene fusions were detected in more than 2 patients.…”
Section: Identification Of Recurrent Cn Changes In Targetable Cancer mentioning
confidence: 95%
See 1 more Smart Citation
“…And although osteosarcoma tumors show a great deal of SV, SVs were found within only 81 of the druggable genes (30 recurrently). The most common genes with an SV were TP53 (29), LRP1B (14), RB1 (8), and FHIT (8). No potentially in-frame gene fusions were detected in more than 2 patients.…”
Section: Identification Of Recurrent Cn Changes In Targetable Cancer mentioning
confidence: 95%
“…Previous studies have analyzed CN alterations in an attempt to identify candidate osteosarcoma driver oncogenes or tumor suppressors (9)(10)(11)(12)(13)(14)(15). These studies have focused on the identification of recurrent changes.…”
Section: Introductionmentioning
confidence: 99%
“…However, its role in sarcomas has been controversial, with some studies suggesting activated β-catenin signaling is important to drive the neoplastic phenotype, while others found an opposite effect (Cai et al, 2014; Cai et al, 2010; Du et al, 2014; Matushansky et al, 2007; Wan et al, 2014). In mesenchymal cell development, β-catenin is precisely regulated at different stages for normal differentiation, raising the possibility that either high or low β-catenin leads to pathology (Chen et al, 2007; Hoffman and Benoit, 2013; Li et al, 2008; Wan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent whole genome sequencing (WGS) and molecular profiling studies undertaken in predominantly pediatric populations have shown high levels of chromosome structural variations, rearrangements resulting from chromothripsis (20-89%) as well as mutation clusters known as kataegis (50-85% of cases) that result in significant disease heterogeneity but few recurrent clinically actionable alterations [5][6][7] . These studies have yielded insights into aberrant signaling pathways such as PI3K/mTOR (24%) 7 , IGF signaling (7%) 6 , and Wnt signaling 8 . However, the efficacy of targeted therapies such as mTOR inhibitors in unselected patient populations with relapsed osteosarcoma has been limited 9,10 .…”
mentioning
confidence: 99%